Handbook of Polymernanocomposites. Processing, Performance and Application Volume A: Layered Silicates - Pandey, Jitendra K.; Reddy, Kummetha Raghunatha; Mohanty, Amar Kumar; Misra, Manjusri; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Volume A of Handbook of Polymer Nanocomposites deals with Layered Silicates. In some 20 chapters the preparation, architecture, characterisation, properties and application of polymer nanocomposites are discussed by experts in their respective fields
Keywords: Chemistry; Polymers; Physics; Chemistry; Polymer Sciences; Physics, general